'n Heilige, algemene kerk - Wim Dreyer (HTS Teologiese Studies/Theological Studies, 2015)
A holy, universal church. The Nicene Creed and the  Apostolicum went through different processes of growth and development. In the early development of both creeds, it is noticeable that articles about ‘the church’ are absent. In this contribution the creeds are examined in terms of their development, the inclusion of the articles on the church, their reception during the 16th century Reformation as well as difficulties in the official Afrikaans translations. It concludes with a short exposition of the Apostolicum’s article on the church (sanctam Ecclesiam catholicam).